Measuring the building blocks of everyday cognition: executive functions and relational reasoning - Richland, Lindsey Engle; Zhao, Hongyang (Frontiers in Psychology, 2023)
Measurement of the building blocks of everyday thought must capture the range of different ways that humans may train, develop, and use their cognitive resources in real world tasks. Executive Function as a construct has been enthusiastically adopted by cognitive and education sciences due to its theorized role as an underpinning of, and constraint on, humans’ accomplishment of complex cognitively demanding tasks in the world, such as identifying problems, reasoning about and executing multi-step solutions while inhibiting prepotent responses or competing desires. As EF measures have been continually refined for increased precision; however, they have also become increasingly dissociated from those everyday accomplishments. We posit three implications of this insight: 1) extant measures of EFs that reduce context actually add an implicit requirement that children reason using abstract rules that are not accomplishing a function in the world, meaning that EF scores may in part reflect experience with formal schooling and Western, Educated, Industrialized, Rich, Democratic (WEIRD; Henrich et al 2010) socialization norms (Alcalá et al., 2018, Gaskins, 2000), limiting their ability to predict success in everyday life across contexts, 2) measurement of relational attention and relational reasoning skills have not received adequate consideration in this context but are highly aligned with the key aims for measuring EFs, and may be more aligned with humans’ everyday high-demand cognitive practices, but 3) relational attention and reasoning should be considered alongside rather than as an additional EF as has been suggested, for measurement clarity.